1.5 Diffuse Parenchymal Lung Disease 2016
DOI: 10.1183/13993003.congress-2016.pa2101
|View full text |Cite
|
Sign up to set email alerts
|

Survival from acute exacerbation of idiopathic pulmonary fibrosis with or without direct hemoperfusion with polymyxin B-immobilized fiber column: A retrospective analysis

Abstract: Objective Acute exacerbations of idiopathic pulmonary fibrosis (AE-IPF) are fatal episodes of acute respiratory worsening of unknown etiology. Previous studies on acute respiratory distress syndrome have shown that direct hemoperfusion with a polymyxin B-immobilized fiber column (PMX-DHP) can have a beneficial effect on the respiratory status. This retrospective study investigated the prognosis and survival outcome of patients with AE-IPF who underwent PMX-DHP. Methods We examined the records of 50 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 13 publications
4
30
0
Order By: Relevance
“…In previous clinical studies, CRP levels were a significant prognostic factor of IPF-AE, suggesting that inflammation may be involved in the pathogenesis of AE. 9,10,38 Lower levels of serum albumin, a negative acute-phase protein and marker of inflammation, were strongly and independently associated with higher mortality in patients with IPF on transplant waiting lists. 8 Factors known to be associated with poor prognosis in IPF-AE are combined diffuse and multifocal patterns rather than peripheral patterns on high- DLco, diffusing capacity of the lung for carbon monoxide; FEV 1 , forced expiratory volume in 1 s ; FVC, forced vital capacity; GPS, Glasgow prognostic score; LDH, lactate dehydrogenase; P/F, partial pressure of oxygen/fraction of inspired oxygen; PFT, pulmonary function test; Pro-BNP, pro-brain type natriuretic peptide; RV, residual volume; TLC, total lung capacity; WBC, white blood cell.…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical studies, CRP levels were a significant prognostic factor of IPF-AE, suggesting that inflammation may be involved in the pathogenesis of AE. 9,10,38 Lower levels of serum albumin, a negative acute-phase protein and marker of inflammation, were strongly and independently associated with higher mortality in patients with IPF on transplant waiting lists. 8 Factors known to be associated with poor prognosis in IPF-AE are combined diffuse and multifocal patterns rather than peripheral patterns on high- DLco, diffusing capacity of the lung for carbon monoxide; FEV 1 , forced expiratory volume in 1 s ; FVC, forced vital capacity; GPS, Glasgow prognostic score; LDH, lactate dehydrogenase; P/F, partial pressure of oxygen/fraction of inspired oxygen; PFT, pulmonary function test; Pro-BNP, pro-brain type natriuretic peptide; RV, residual volume; TLC, total lung capacity; WBC, white blood cell.…”
Section: Discussionmentioning
confidence: 99%
“…106 A more recent retrospective Japanese study suggests that survival in those patients who received PMX may have been improved. 107 PMX is not a currently accepted treatment for AE-ILD, but such research may support the role of infections as antigenic stimulus in the setting of AE.…”
Section: Antimicrobial Treatment Studiesmentioning
confidence: 99%
“…Data on the effective use time and frequency of PMX-DHP of AE-IPF are lacking; additionally, no randomized clinical trials have studied this approach. However, one study reported that PMX-DHP was more effective when applied within 1 week of acute symptom exacerbation onset when the underlying IPF was more severe [1,2]. Here, we reported two cases of AE-IPF that were treated by PMX-DHP.…”
Section: Discussionmentioning
confidence: 73%
“…AE-IPF is typically associated with an extremely poor prognosis, with the reported 90-day mortality rate being approximately 60%-80% [8]. Steroids and immune-suppressants have been used to treat AE-IPF, but there are currently no effective treatments [1]. PMX-DHP was developed to remove plasma endotoxins from patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation